Revolutionizing Retail Operations: AI and ML Implementation - H, Lakshmi.; H K, Keerthi; Ajay, Shilpa (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
Aim: This paper highlights the transformative influence of the integration of artificial intelligence (AI) and machine learning (ML) technologies on the retail landscape in India, focusing on their role in enhancing customer experiences, driving sales, and reshaping retail operations and raising awareness about the ethical considerations associated with the integration, for sustainable growth and customer trust. Methodology: Systematic review research is conducted to analyse and collect data from scholarly research databases and industry analysis. Selected research papers and reports were scrutinized, and the analysis considered their research design analysis, methodologies utilized, and data sources, to provide a comprehensive overview of the use of AI and ML in retail commerce. Findings: The transformative capacity of Artificial Intelligence (AI) and Machine Learning (ML) within the retail sector is discussed in the findings. AI and ML technologies have a strong and deep ability to enrich user experiences through personalized recommendations, optimize inventory management, streamline supply chains, implement efficient pricing strategies, and enhance consumer service. The study discusses the limitations and scope for ethical considerations during the integration of AI and ML within the retail landscape. Conclusion: This study emphasizes the importance of AI and ML in shaping the future scope of the retail landscape. By discussing the disruptive potential, and ethical implications of AI and ML technology integration, it provides invaluable insights to retailers, policymakers, and industry stakeholders, urging them towards continued exploration and investment in the retail ecosystem.